2011
DOI: 10.1111/j.1469-0691.2010.03406.x
|View full text |Cite
|
Sign up to set email alerts
|

Lower incidence of catheter-related bloodstream infection in subclavian venous access in the presence of tracheostomy than in femoral venous access: prospective observational study

Abstract: Guidelines for the prevention of catheter-related bloodstream infection (CRBSI) recommend subclavian rather than femoral venous access to minimize the risk of CRBSI. However, they do not address the issue of CRBSI with subclavian venous access in the presence of tracheostomy, where the incidence of CRBSI has been found to be higher than without tracheostomy. In this study, we found lower CRBSI in subclavian venous access in the presence of tracheostomy than in femoral venous access (3.9 vs. 10.1 CRBSI per 1000… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Afterwards, we found that internal jugular venous site by central access and tracheostomy had a higher CRBSI risk than femoral venous site [44] . In addition, we found a lower CRBSI risk in the subclavian venous site with tracheostomy than in femoral venous site [45] . Besides, we found a higher CRBSI risk in internal jugular venous site by posterior access with tracheostomy than without tracheostomy [46] .…”
Section: Risk Of Crbsi According the Existence Of Tracheostomymentioning
confidence: 50%
“…Afterwards, we found that internal jugular venous site by central access and tracheostomy had a higher CRBSI risk than femoral venous site [44] . In addition, we found a lower CRBSI risk in the subclavian venous site with tracheostomy than in femoral venous site [45] . Besides, we found a higher CRBSI risk in internal jugular venous site by posterior access with tracheostomy than without tracheostomy [46] .…”
Section: Risk Of Crbsi According the Existence Of Tracheostomymentioning
confidence: 50%
“…One study assessed the use of the subclavian vein in the presence of tracheostomy in comparison to the femoral vein. The "subclavian + tracheostomy" group presented lower incidence of CLABSI when compared to "femoral without tracheostomy", 3.9 vs. 10.0 CLABSI episodes/1,000 catheter days, while there was a tendency for the incidence of CLABSI in the "subclavian + tracheostomy" group to be lower, 3.9 vs. 11.2I CLABSI/1,000 catheters-days 40 . Level of evidence: 3.e.…”
Section: Discussionmentioning
confidence: 84%
“…Extra strategies added to already implemented care concerning the insertion and maintenance of catheters were tested as a means to lower risk of colonization and infection of CVCs 14 , 17 , 27 , 30 , 34 - 36 , 40 - 41 .…”
Section: Discussionmentioning
confidence: 99%
“…Several studies found that catheter related local infection incidence was higher for femoral than for internal jugular or subclavian access routes. 3 Anaesthesia was maintained with volatile agents. Sevofurane when compared with i.v.…”
Section: Discussionmentioning
confidence: 99%